Sistem Pendukung Keputusan Pemilihan Kepala Cabang PDAM Tirtanadi Cabang Padang Bulan Menerapkan Metode MOORA - Laila Mustika; Sari Dewi Andini; Deny Juliarmanda; Natalia Silalahi (JURIKOM (Jurnal Riset Komputer), 2018)
The selection of branch heads at a local water utility company is a process that requires precision and accuracy in its election. The results obtained should be better for the development of the organization in the future. But if the election is not right then, can be fatal for the continuity of the way an organization. For that the application of computer systems, in this case, decision support system is very necessary because in decision support systems can be applied methods that can produce better decisions, such as using MOORA method is Optimizing Multi-Objective Method with Ratio Analysis (MOORA). MOORA method is one MADM method that can perform calculations on the value of attribute criteria for prospective branch heads and produce a decision more precisely